Impact of 5 MWp Solar Power Plant Interconnection on Power Flow and Short Circuit Interruption in the 20 kV Medium Voltage Network at Area X Power System - Hanindito Titah Prameswara; Amien Rahardjo; Nadyanti Larasati; Faiz Husnayain (Jetri : Jurnal Ilmiah Teknik Elektro, 2020)
One example of the application of new renewable energy that is currently developing is solar power plant. Based on data from Rencana Usaha Penyediaan Tenaga Listrik (RUPTL) PT PLN (Persero) 2019-2028, it is stated that the potential of solar energy in Indonesia is 207,898 MW (4.80 kWh / m2 / day) and only 78.5 MW of capacity installed in Indonesia. In this study, a 5 MWp solar power plant was interconnected with a 20 kV medium-voltage network of Area X as one of the renewable energy applications in Indonesia. Interconnection studies include power flow analysis and three phase short circuit fault analysis. In the analysis of the power flow results obtained that the Solar Power Plant system is capable of supplying the load requirements to the system of 5,000 kW active power. It was also found that interconnection of solar power plant with the system resulted in an increase in the voltage level of each bus in the system by 0.08 to 1.41%, as well as changing the percentage of component loading by 0.01% -93.01%. The results of the three-phase short-circuit fault analysis show that the interconnection of the solar power plant system has a short-circuit fault current value of 5.70-7.01 kA, so the fault current value for the whole bus is still far below the value of the short-circuit current capacity of the protection system's short circuit worth 25 kA. The results of the interconnection study showed that interconnection of a 5 MWp solar power plant system with a 20 kV medium voltage network Area X can be carried out.